A one-year follow-up study of treatment-compliant suicide attempt survivors: relationship of CYP2D6-CYP2C19 and polypharmacy with suicide reattempts - Eva M. Peñas-Lledó; Sebastien Guillaume; Fernando de Andrés; Ana Cortés-Martínez; Jonathan Dubois; Jean Pierre Kahn; Marion Leboyer; Emilie Olié; Adrián LLerena; Philippe Courtet (Translational Psychiatry, 2022)
Abstract This study of a cohort of 1-year treatment-compliant survivors of a suicide attempt examined for the first time whether a high CYP2D6-CYP2C19 metabolic capacity (pharmacogenes related to psychopathology, suicide, and attempt severity) and/or polypharmacy treatments predicted repeat suicide attempts, adjusting for sociodemographic and clinical factors as confounders. Of the 461 (63% women) consecutively hospitalized patients who attempted suicide and were evaluated and treated after an index attempt, 191 (67.5% women) attended their 6- and 12-month follow-up sessions. Clinicians were blinded to the activity scores (AS) of their genotypes, which were calculated as the sum of the values assigned to each allele (CYP2C19 *2, *17; CYP2D6 *3, *4, *4xN, *5, *6, *10, wtxN). No differences were found in polypharmacy prescription patterns and the variability of CYP2D6 and CYP2C19 genotypes between adherents and dropouts, but the formers were older, with a higher frequency of anxiety and bipolar disorders and fewer alcohol and substance use disorders. The risk of reattempts was higher for CYP2D6 ultrarapid (AS > 2) metabolizers (β = 0.561, p = 0.005) and violent suicide survivors (β = −0.219, p = 0.042) if the attempt occurred during the first 6-month period, individuals with an increased number of MINI DSM-IV Axis I mental disorders (β = 0.092, p = 0.032) during the second 6-month period and individuals with a combined high CYP2D6-CYP2C19 metabolic capacity (AS > 4) (β = 0.345, p = 0.024) and an increased use of drugs other than antidepressants, anxiolytics-depressants and antipsychotics-lithium (β = 0.088, p = 0.005) in multiple repeaters during both periods. CYP2D6 and CYP2C19 rapid metabolism and polypharmacy treatment for somatic comorbidities must be considered to prevent the severe side effects of short-term multiple suicide reattempts after a previous attempt.